Philosophy study aid - Kornienko, A. A. D. Sc. Professor of the TPU 1941- (TPU Publishing House, 2023)
The textbook consists of ten sections aimed to promote understanding of contemporary philosophical views on fundamental aspects of the history and theory of philosophy. The textbook is recommended for international students studying with the medium of English language in all bachelor, academic exchange and postgraduate programmes of TPU.